Evaluation of the challenges in water governance through citizen's perception and Water Quality Index: a case study of a fast-growing city in India - A. Navaneeth; P. Sreeda; T. M. Vishnu Maya; P. S. Sanusree; P. S. Harikumar (H2Open Journal, 2021)
Urban water governance (UWG) plays an important role to ensure safe and sufficient water availability in cities. In developing countries, citizen centric studies, which are important to understand the ground-level scenario and the existing UWG, are often not conducted due to the lack of manpower or infrastructure. Indian cities are rapidly growing, and there is a need to revisit the existing UWG scenario in its cities. Therefore, as a first step, this study evaluates the UWG challenges in Kozhikode, Kerala, based on citizen perception and drinking water quality. The present study reports the findings from face-to-face interviews conducted (using structured questionnaires) to evaluate the knowledge of citizens in the basic areas of water resources management and conservation (n = 180) and the analysis of water samples from household sources (n = 261). The Water Quality Index (WQI) was computed and analyzed using the Geographic Information System (GIS). The WQI map identified the vulnerable areas requiring focused intervention to improve water quality. A poor awareness among the respondents, especially regarding the local water resources, was identified from the interviews. However, on a positive note, the citizens are willing to bridge this knowledge gap. Thus, involving citizens and understanding the issues at the ground level will aid in improving the UWG in cities. HIGHLIGHTS The questionnaire survey and water quality assessment helped to know the citizens' perception of the major water governance challenges.; Knowledge gap and lack of coordination of multiple stakeholders are the major governance challenges to be addressed.; Citizens' engagement and stakeholder interaction through effective data transfer strengthen the water governance aspects of a city.;